Impacto da Dança Sênior® no equilíbrio de idosos com declínio cognitivo e análise da influência da farmacoterapia - Miyashiro, Isabela Kaori [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Background: The aging process is the loss of functions that can cause balance and cognitive impairment, some drugs used by elderly people with cognitive decline may increase the risk of falling. Therefore, it is important to seek ways to promote healthy aging, and the Senior Dance® is a strategy that stands out to provide physical and cognitive benefits. Aims: Evaluate the impact of Senior Dance® on the balance of elderly people with cognitive decline and analyze the influence of pharmacotherapy on this aspect. Methods: The study consisted of five participants. Information was collected regarding the medication used, and the balance assessment was performed by using the Berg Balance Scale (BBS) before, during and after the intervention. The Senior Dance® was performed for four months, totaling 16 meetings of 60 minutes. Data were processed in Excel® and presented through absolute frequency and percentage distribution. Results: Among the participants, there was a predominance of the age 61-90 years old, female, sedentary and no smokers or alcoholics. Three participants showed improvement in BBS and two of them got worse. During the intervention, there was an increase in medication consumption, prevailing drugs for the nervous and cardiovascular system. Discussion: There are studies showing that Senior Dance® is able to improve balance; few stimulation, short time intervention or the influence of pharmacotherapy may result in less effective intervention. Conclusions: Senior Dance® had a positive impact on the balance of most participants, but pharmacotherapy can negatively influence its results.

Introdução: O envelhecimento é um processo de perda de funções que pode trazer prejuízos ao equilíbrio e ao cognitivo, além disso alguns fármacos usados por idosos com declínio cognitivo podem aumentar o risco de quedas. Portanto é importante buscar formas de promover o envelhecimento saudável, sendo a Dança Sênior® uma estratégia que se destaca por proporcionar benefícios físicos e cognitivos. Objetivo: Avaliar o impacto da Dança Sênior® no equilíbrio de idosos com declínio cognitivo e analisar a influência da farmacoterapia neste aspecto. Método: O estudo foi composto por cinco participantes. Foram coletadas informações quanto a medicação utilizada, e a avaliação do equilíbrio foi feita através da Escala de Equilíbrio de Berg (EEB) antes, durante e após a intervenção. Foi realizada a Dança Sênior® por quatro meses, totalizando 16 encontros de 60 minutos. Os dados foram processados no Excel® e apresentados por meio de distribuição de frequência absoluta e percentual. Resultado: Dentre os participantes houve predominância da faixa etária de 61-90 anos, sexo feminino, sedentário e nenhum tabagista e etilista. Três participantes apresentaram melhora na EEB e dois deles apresentaram piora. Durante a intervenção houve aumento do consumo de medicamentos, prevalecendo fármacos para sistema nervoso e cardiovascular. Discussão: Existem estudos mostrando que a Dança Sênior® é capaz de melhorar o equilíbrio; poucos estímulos, curto tempo de intervenção ou a influência da farmacoterapia podem resultar em menor eficácia da intervenção. Conclusão: A Dança Sênior® apresentou impacto positivo no equilíbrio da maioria dos participantes, porém a farmacoterapia pode influenciar negativamente seus resultados.
Impact of Senior Dance® on the balance of elderly with cognitive decline and analysis of the influence of pharmacotherapy
Keywords: Dancing; Postural balance; Aged; Cognitive dysfunction; Drug therapy; Dança; Equilíbrio postural; Idoso; Farmacoterapia; Declínio cognitivo